'Dream of a green tomorrow, act today': an exploratory study on environmental involvement and practices among Indian consumers. (18th May 2022) - Sudhagar, D.P.; Binu, T.D. Mary; Sheeja, M.S.
The aim of the present study is to investigate the environmental involvement and practices of Indian consumers. The survey method was used with the help of a structured online questionnaire. The data was collected from the stakeholders following the convenience sampling approach. The results of the overall EIP among Indian consumers indicate a need for immediate intervention from the environmental protection authorities to enhance the EIP. The study also identified a list of improvements required in the areas of EIP. The present study offers information for the government, policymakers, and policy implementers to understand the scenario and formulate strategies to take corrective action. The study also contributes to the theory in terms of a unique instrument to capture the EIP from the stakeholders and literature to the emerging area of, 'environment'.